The comparative-historical method of studying biographies: heroes of the Great Patriotic War Tulush Kechil-ool and Bauyrzhan Momyshuly - Kilash, Rassul Zh.; Otepova, Gulfira E.; Karimova, Anara E. (The New Research of Tuva, 2022)
The article makes an attempt at historical comparison of the biographies of the Heroes of the Soviet Union Tuvan Tulush Kechil-Ool and Kazakh Bauyrzhan Momyshuly. The use of the comparative historical method in analyzing their biographies is based on Plutarch’s principle of binarity and the unity of J. M. Cooper’s notion of chronology of biographies. Comparison allows the authors to reveal similarities and differences in the heroes’ personalities. Bothbelonged to the Turkic peoples, took the professional path before joining the army, had a military career of an officer, were famous for their heroic deeds, personal qualities, and were awarded the distinction of the Hero of the Soviet Union. The unity of their lifepaths is explained in connection with the history of the country and people, and also with important historical events. Until now, historians have not paid enough attention to the fact that when both commanders were nominated for the title of Hero of the Soviet Union during the Great Patriotic War, they did not receive this title at that time. Tuvan historians have put forward a hypothesis that the reason for this was Kechil-ool’s belonging to the repressed clan of Adyg-Tyulyushi. As for Momyshuly, Kazakhstani historians have not yet fully clarified this situation. Both officers were outstanding representatives of their peoples, and their memory is carefully preserved, and their lives are in the focus ofhistorians’ studies. A comparative historical analysis of the biographies of two outstanding representatives of the Tuvan and Kazakh peoples showed their role in the history of their peoples, and how lives are inclose connection with the historical process.